2021
DOI: 10.1038/s41598-021-93761-0
|View full text |Cite
|
Sign up to set email alerts
|

Important gender differences in psychosomatic and school-related complaints in relation to adolescent weight status

Abstract: Underweight or overweight in adolescence is linked to several adverse health outcomes. Less evidence exists about the association between weight status and school-related psychosocial characteristics in high income countries. We sought to investigate the relationship between weight status and psychosomatic and school-related complaints with a focus on gender differences. The study is a cohort of 18,462 adolescents (12–19 years; 51% girls) conducted in Sweden. The associations between weight status and psychoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…In this study, men have fewer psychosomatic complaints than women. Previous research reported that women have higher psychosomatic symptoms compared to men ( Östberg et al, 2006 ; Brooks et al, 2021 ), which supports our results for translated versions of PSSS.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, men have fewer psychosomatic complaints than women. Previous research reported that women have higher psychosomatic symptoms compared to men ( Östberg et al, 2006 ; Brooks et al, 2021 ), which supports our results for translated versions of PSSS.…”
Section: Discussionsupporting
confidence: 92%
“…Further research may highlight a specific link between (a) the presence of PSCs, (b) minor behavioral issues that if left undetected may transform into (c) formal CD, and the underlying mental health difficulties that may contribute to all three. For example, in another recent study examining the same Swedish cohort as the present study, it was demonstrated that underweight vs. overweight boys and girls had higher PSCs (e.g., headache and pain in the hips) and that these complaints significantly contributed to mental health difficulties (e.g., anxiety, depression, and generally ‘feeling low’), although this study did not consider DSM5 CD-related behavioral issues [ 27 ]. Another Swedish study from a different, large cohort, found that subjective health complaints in adolescents were predictive of higher stress levels and mental health issues [ 28 ].…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, girls with obesity seemed to be at higher risk of getting anxiety and depression compared to boys with obesity [ 47 ]. Furthermore, girls and boys who are overweight or obese are at increased risk of bullying and academic failure, which creates a burden well into their adulthood [ 48 ].…”
Section: Clinical Consequencesmentioning
confidence: 99%